Investor’s Obligations in Default Dispute of Build Operate Transfer Agreement for Market Revitalisation - Hardiyanti, Lesha; Taupiqqurrahman, Taupiqqurrahman (Jurnal Ius Constituendum, 2024)
This research aims to find out the position of investor in the build operate transfer (BOT) agreement and the responsibility of investor due to default in the BOT agreement for market revitalisation. The government cooperates with investor to overcome capital difficulties. But there are still many default disputes in the implementation of the market revitalisation BOT agreement. Example, in Cikampek I Market, Metro City Market and Cibitung Main Market. This research is urgent to conduct because default disputes can result in financial and reputational losses for the government, and have negative impact on society. This research method is normative legal research. The novelty of this research is to explore the position of investors in BOT agreements in the face of possible negative impacts on economic, social, environmental and the application responsibilities for defaults by providing examples of real cases. The result of this study is that in the BOT agreement, the investor's position includes financing in development, management with risk management, transfer to ownership. The investor's responsibility due to the default of the market revitalisation BOT agreement includes compensation with dispute resolution for postponement of obligations in the addendum, fines, termination of the agreement.